2001
DOI: 10.1177/0734242x0101900616
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gas transport in soil adjacent to an old landfill: factors governing emissions and methane oxidation

Abstract: Field investigations of lateral gas transport and subsequent emissions in soil adjacent to an old landfill in Denmark have been conducted during a one-year period. A significant seasonal variation in the emissions with high carbon dioxide and low methane fluxes in the summer (May to October) was observed. This was attributed to methane oxidation. Diumal measurements during a drop in barometric pressure showed that the fluxes of landfill gas changed dramatically within a very short time. The concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 34 publications
5
83
0
7
Order By: Relevance
“…The soil was sampled at a test station on the landfill border where the average methane emission was 25 mmol/m 2 /hr (maximal emission was 189 mmol/m 2 /hr) measured during a 1-yr field campaign. 9 The soil was sampled in 5-cm intervals from the surface to 30 cm depth and in 10-cm intervals from 30 -90 cm below the surface. Soil samples were collected using a hand auger and stored at 4°C in darkness in closed containers to avoid dehydration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil was sampled at a test station on the landfill border where the average methane emission was 25 mmol/m 2 /hr (maximal emission was 189 mmol/m 2 /hr) measured during a 1-yr field campaign. 9 The soil was sampled in 5-cm intervals from the surface to 30 cm depth and in 10-cm intervals from 30 -90 cm below the surface. Soil samples were collected using a hand auger and stored at 4°C in darkness in closed containers to avoid dehydration.…”
Section: Methodsmentioning
confidence: 99%
“…4 -6 Field studies have shown that between 10 to 100% of the emitted methane can be oxidized on an annual basis. [7][8][9] Furthermore, methane flux emission measurements have shown negative fluxes, indicating uptake of atmospheric methane and proving that in some cases, landfill cover soils may even serve as sink for atmospheric methane. 10 -12 Although attenuation of methane in landfill covers has been intensively studied to evaluate the contribution of landfills to global warming, there is little research concerning the potential for attenuation of VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…The mean CH 4 oxidation capacities at the four locations were 19.5, 26.6, 14.4, and 25.2 %. However, Christophersen et al (2001) measured CH 4 oxidation from the Skellingsted landfill in Denmark during summer and winter. They found that in summer 100 % of the CH 4 was oxidized, while the oxidation capacity in winter was 89 %.…”
Section: Ch 4 Oxidation Capacitymentioning
confidence: 99%
“…The concentrations of three main soil gases were investigated: CH 4 , CO 2 , and O 2 . The combination of surface LFG emissions and soil gas concentration profiles was used to estimate CH 4 oxidation in the soil cover in accordance with Christophersen et al (2001).…”
Section: Experimental Designmentioning
confidence: 99%
“…The thickness of biofilter �mixture of com post, wood fibers, and peat� required for 90% methane oxidation efficiency was 54% higher at 22°C than at 30°C with a maxi mum limit for optimum biocover operation of approximately 35°C based on laboratory tests �Streese-Kleeberg and Stegmann 2008�. Methane flux from cover soils at landfills in Northern Eu rope decreased significantly in spring/summer months �with maximum soil cover temperatures of approximately 24-27°C� compared to the measured values in fall/winter months �with minimum soil cover temperatures of approximately 0 -10°C� �Boeckx et al 1996;Börjesson et al 2001;Christophersen et al 2001�.…”
Section: Introductionmentioning
confidence: 99%